The Impact of Management on the Organizational Efficiency - Liudmyla SYTNYK; Ielyzaveta SHAKHOVALOVA (Communications of International Proceedings, 2021)
In the article, the management efficiency of an organization is shown. The main components of the organization's success over an extended period are identified. The connection of management efficiency with the process of determining the efficiency of capital investments, initiatives of scientific and technological progress and new equipment is revealed. Behavioral and neoclassical approaches to the definition of production efficiency, the social cost of monopoly, investment conditions, the investment level that maximizes profit are characterized. In addition, various approaches to criteria of management efficiency are disclosed. The process of evolution of organizational structures from the most well-known types to new types with new approaches to the problems of making managerial decisions (adhocracy, multidimensional, participatory organizational structures), their advantages and disadvantages, has been investigated. The features of a highly efficient organization and its difference from a traditional organization are revealed. The choice of the system of indicators for assessing the internal efficiency of the organization has been substantiated. The unproductiveness of the Ukrainian economy, the presence of crisis phenomena, and influence of demand on production efficiency are shown. The main indicators (criteria) of management efficiency as well as social indicators of increasing the welfare of the population were chosen to reduce the cost and prices of goods. It is proposed to strengthen responsibility for the organization's efficient performance, for the managerial decisions and their consequences; to necessitate the state regulation of prices by setting fixed prices (tariffs) and ceiling levels of prices (tariffs) or maximum deviations from state prices (tariffs). State regulation must be carried out by introducing a marginal level of profitability as a percentage of the cost price for producers and a marginal level of trade and supply-sell margins as a percentage of the wholesale price.
Keywords: Management Efficiency; Organization; Production; Capital Investments; Investment; Management Efficiency Criteria.